2021
DOI: 10.2519/jospt.2021.9864
|View full text |Cite
|
Sign up to set email alerts
|

Dry Needling Adds No Benefit to the Treatment of Neck Pain: A Sham-Controlled Randomized Clinical Trial With 1-Year Follow-up

Abstract: neck pain. 42,47 The most effective physical therapy treatments for neck pain include exercises that strengthen the neck, scapulothoracic region, and shoulder 32 and manipulation and mobilization of the thoracic spine. 30 However, there is conflicting evidence on whether these interventions are more effective when combined or used alone. 16,23,31 Dry needling is a common treatment for musculoskeletal conditions such as neck pain, despite a lack of clinical trials examining its effectiveness. 17,18,24,25,34 Dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Needle therapy, including dry needling, for chronic neck pain is usually used with more than one filament needle to needle into the MTrPs directly or nearby areas; however, the effectiveness of dry needling on chronic neck pain is equivocal, recently reported by a long-term follow-up trial [ 37 ] and a meta-analysis study [ 38 ]. Furthermore, given that most people are high responders to needle pain [ 39 ], remote therapy and needle-less methods are the better options for health care.…”
Section: Discussionmentioning
confidence: 99%
“…Needle therapy, including dry needling, for chronic neck pain is usually used with more than one filament needle to needle into the MTrPs directly or nearby areas; however, the effectiveness of dry needling on chronic neck pain is equivocal, recently reported by a long-term follow-up trial [ 37 ] and a meta-analysis study [ 38 ]. Furthermore, given that most people are high responders to needle pain [ 39 ], remote therapy and needle-less methods are the better options for health care.…”
Section: Discussionmentioning
confidence: 99%
“…The current study results agree with those of previous studies that compared the efficacy of DN with that of other interventions for CMNP. A recent randomised controlled trial (RCT) by Gattie, Cleland [ 42 ] on the efficacy of DN and manual therapy (MT) in CMNP revealed that MTrP-DN showed no substantial or clinically meaningful advantages in disability reduction or pain alleviation compared to MT and exercise in both short term and long-term follow-ups. Onat, Polat [ 1 ] compared the efficacy of DN and kinesio-tape in mechanical neck pain and found that the latter was superior to DN in improving the flexibility of the neck region and reducing the disability of CMNP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence does not support a long-term added benefit of DN to traditional therapeutic modalities for neck pain. 76,77 Thus, it should be explored if the addition of DN to tailored sensorimotor training can provide additional gains in sensorimotor control measures. Also, a reduction in pain intensity (which was close to be clinically meaningful) was observed after DN; which is consistent with previous studies targeting the local source of altered cervical afferent input in people with neck pain and impaired sensorimotor function.…”
Section: Discussionmentioning
confidence: 99%